Zn1−xSixO: Improved optical transmission and electrical conductivity. Issue 7 (May 2017) - Srivastava, Tulika; Sadanandan, Aswin; Bajpai, Gaurav; Tiwari, Saurabh; Amin, Ruhul; Nasir, Mohd.; Kumar, Sunil; Shirage, Parasharam M.; Biring, Sajal; Sen, Somaditya
Abstract: Si addition in ZnO lattice significantly improves electrical conductivity. The extra charge of Si 4+ ion (in comparison to Zn 2+ ) attracts more oxygen in the lattice and reduces oxygen vacancies. Reduction of oxygen vacancies (defects) reduces strain in the lattice. Transparency of visible light (<3.0 eV) improves due to reduction of these defects in the wide bandgap ( 3.3 eV: UV) of ZnO. Extra charge of Si 4+ enhances carrier density in the ZnO lattice. Improved carrier density, reduced strain facilitate transport of carriers and therefore conductivity increases. Si incorporation also makes the samples moisture resistant. The material becomes more robust to operate in adverse humid conditions. An ideal transparent conductive oxide (TCO) should be conductive, transmit visible light and able to sustain humid conditions. All these properties are observed in Zn(1−x) Six O material.